Bayesian games with unawareness and unawareness perfection - Martin Meier; Burkhard C. Schipper (University of California, Department of Economics, 2013)
Applying unawareness belief structures introduced in Heifetz, Meier, and Schipper (2013a), we develop Bayesian games with unawareness, define equilibrium, and prove existence. We show how equilibria are extended naturally from lower to higher awareness levels and restricted from higher to lower awareness levels. We apply Bayesian games with unawareness to investigate the robustness of equilibria to uncertainty about opponents' awareness of actions. We show that a Nash equilibrium of a strategic game is robust to unawareness of actions if and only if it is not weakly dominated. Finally, we discuss the relationship between standard Bayesian games and Bayesian games with unawareness.
Keywords: C70; C72; D80; D82; 330; unawareness; awareness; type-space; incomplete information; Bayesian games; equilibrium; perfection; undominated equilibrium; weak dominance; admissibility; inattention